Bacterial Contamination at Whiteleg Shrimp (Litopeanaeus vannamei) in Aquaculture - Mashuri Masri -; Eka Sukmawaty; Fatmawati Nur; Suriani Suriani (Jurnal Biodjati, 2021)
Indonesia has a very high biodiversity, which has later become one of the natural products of interest to the international community, including fishery products. One of the high-demand Indonesian fishery products is whiteleg shrimp Litopeaneus vannamei. However, safety food Exported whiteleg shrimp products must meet the criteria, including free from bacterial contamination such as Escherichia coli, Salmonella, Vibrio cholera. This study attemptted to analyze E. coli, Salmonella, V. cholerae contamination in 3 ponds in Bojo, Cilellang, and Palanro Village in District Malusetasi, Barru Regency, South Sulawesi. Two samplings for each pond were conducted in the morning were pond water and  fresh whiteleg shrimp. SNI 2728-2018 specifies the quality and safety requirements for fresh shrimp. This standard applies to whole or headless fresh shrimp handled from fresh shrimp and does not apply to fresh shrimp that has undergone further processing. Based on SNI 2728-2018, the E. coli test showed positive in Cilellang Village (sample A) with 11 MPN/g, negative in Palanro Village (sample B) and in Bojo village (sample C) with the value of <2 MPN/g. Escherichia coli test showed positive in sample D (Vannamei shrimp in Cilellang Village) and sample E (Vannamei shrimp in Palanro Village) with 2.0 MPN/g, 17 MPN/g, respectively. Only sample F (Vannamei shrimp in Bojo village ) showed a negative result. As for the Salmonella test, positive results showed in sample A, while sample B and sample C showed negative results. The Vibrio cholerae test showed negative at all samples. . This study concludes that Whiteleg shrimp from ponds in Mallusetasi District is classified as safe for consumption.